Effects of spontaneous music tempo on running performance - Kreitinger, Jerica (My University, 2010)
Exercise intensity has been shown to increase with the use of music. Objective: To determine if spontaneous music tempo affected running performance (eg. Velocity, heart rate, ratings perceived exertion - RPE, and VO2). Methods: Fifteen apparently healthy college aged subjects ran two, 31 minutes experimental runs on an indoor 200 meter track. The subjects listened to a 31 minute playlist created by the investigator for one of the runs, and 31 minute minutes of no tempo music for the other run. The playlist consisted of two songs having no-tempo (0 bpm), two songs with slow tempo (<100 bpm), two songs with moderate tempo (100-129 bpm), and two songs with fast tempo (>130 bpm). The order of the runs was randomized. Oxygen consumption (VO2) was integrated every 30 seconds. Velocity was calculated by manually timing 100 meter split times. HR and RPE were recorded at the end of each of the songs. Results: There was a significant increase in running velocity when faster tempo songs were being played. There was no significant difference found in HR, VO2, or RPE in relationship to the tempo being played. However, practical significance was noted as there was not an increase in RPE with the increase in velocity. Conclusions: Music can be used while running to increase the intensity or velocity of the run. However, the effects of music on running performance are not as distinct as cycling due to mechanical constraints of running. Due to the mechanical constraints of running, it is thought that music increases running intensity through general arousal to the beat or tempo.
Keywords: Running -- Physiological aspects; Music -- Physiological effect